AB0793 Clinical Audit of NICE Guidance for Management of Osteoarthritis. (10th June 2014) - Ahmed, S.A.; Sanders, P.A.; Watson, P.
Abstract : Background: Osteoarthritis (OA) is a chronic degenerative condition, which increases in prevalence with age and is a leading cause of disability worldwide. There is currently no cure for OA and treatment focuses on alleviating pain, stiffness and improving the function of the affected joints. Objectives: To audit the management of patients suffering from osteoarthritis (OA), in secondary care, using the National Institute for Health and Care Excellence (NICE) Clinical Guidance 59 (CG59, UK). Methods: A retrospective study was performed of patients attending the rheumatology department at the University Hospital South Manchester for OA between October 2012 and December 2012. This was achieved through initial analysis of electronic clinic letters, using the key word "Osteoarthritis", excluding patients suffering from other forms of arthritis and rheumatological disorders. The remaining patient records were compared to an extensive pre-determined pro forma based on NICE guidelines on OA management (CG59). Results: 32 patients suffering with OA and no other rheumatological disorders were identified from a group of 142. The patient ages ranged from 47 to 96 years and 87.5% of patients were female. 100% of patients' quality of life was assessed adequately, with 100% of patients being provided with correct verbal information but only 26.5% provided with written information. 43.7% of patients were offered self-management strategies (exercise, weight loss, suitable footwear). 73% of patients on non-steroidal anti-inflammatory drugs (NSAIDs) were co-prescribed a proton pump inhibitor (PPI), whilst 83% of patients on aspirin were prescribed a non-NSAID. Only 53% of applicable patients were offered topical NSAIDs as pharmacotherapy. 3% of patients were offered glucosamine by the clinician, despite guidance stating otherwise. Conclusions: The department excelled in holistic management of OA but was less effective at promoting the core treatments and self-management strategies for OA, prior to pharmacological or surgical interventions. PPIs were under prescribed at the department. More importance should be given in promoting the core treatments (information access, exercise and activity, weight loss) and self-management strategies when managing OA, and PPIs must be co-prescribed with NSAID therapy. Clinicians should remember to implement the more general and non-pharmacological aspects of NICE guidance for OA. The department should aim to re-audit in a year's time. References: Arthritis Care. OA nation. London: Arthritis Care, 2004. Issa, SN & Sharma, L. Epidemiology of Osteoarthritis: An Update. Current Rheumatology Reports, 2006; 8:7–15. National Institute for Health and Clinical Excellence: Osteoarthritis- Full Guidance. London: NICE, 2008. Acknowledgements: I received assistance in patient data collection from Mrs Maureen Connolly, medical secretary, and from Jonathan Swift, Clinical Audit Department, University Hospital of South Manchester Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1195